Features of the Implementation of Integrated Marketing Communications: Resistance to Change - Timofeeva, Alla A.; Bulganina, Svetlana V.; Fomenko, Natalia M.; Khachaturova, Margo S.; Nekrasova, Marina L.; Zakharova, Elena N. (International Review of Management and Marketing, 2016)
The issue of communication in the marketing activities more relevant for Russian production companies when they do not have sufficient funds for modernization, restructuring and competitiveness in the market. Over the past 20 years of the Reformation in the Russian Federation there were fundamental modifications to the communicative strategies of most industrial and commercial companies, which are characteristic features of the situation and changes in the approaches of realization of marketing activities. Manual production and trading companies have invested heavily, both in the creation of new products and the creation of new effective methods of promotion. Effective marketing communications are due to its openness, transparency relationships, initiative on the part of industrial and trading companies, building loyalty programs in relation to the final consumer of finished products. Keywords: marketing, marketing communications, methods of promotion, market conditions JEL Classifications: M11; M31